Perancangan Aplikasi Kamus Istilah Programming Dengan Metode Interpolation Search Berbasis Website - Santho Baido Hasian Manullang; Imam Saputra; Fince Tinus Waruwu (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
For students, especially informatics majors, if they plan to study programming, they should first know the terms in it. Learning programming can sharpen problem-solving skills and create creative reasoning. The problem is that learning programming is relatively difficult and has many obstacles. Some of the obstacles include difficulty in understanding some of the terms found in the programming field. If ignored, there will be ambiguity about the term and it will be more difficult to learn it. The solution to this problem is to provide digital information media in the form of a translation dictionary in the form of a website-based application that is implemented online with the concept of the Interpolation Search method. In this method, the process is that theoretical data collection is also calculated using the interpolation method and then the index position is determined, and the results of the same index between theoretical and practical tests are carried out by producing a predetermined scheme. This research will produce a website-based application that translates programming terms with simple, effective, and accurate searches.